A caracterização da função afim como ferramenta na modelagem de problemas matemáticos - Silva, Francisco Eudes da (2015)
This paper deals with the importance of characterization of the affine function as a tool for modeling problems situations, and propose the use of mathematical modeling methodology as motivating source for the study of affine function in high school.To this end, it started with a theoretical reading based on several authors and official stamp documents as the DCN, PCN to high school. Then it offers two scenarios which can be used as mathematical modeling activities describing each step thereof. In the first chapter is made a reflection on the high school in Brazil and the teaching of mathematics. The second chapter presents the theoretical and historical basis for the study of functions in particular the affine function. Emphasis is given to the fundamental theorem of proportionality and the characterization of the same theorem and applications that function in studies of arithmetic progressions, Geom tangent analysis to a curve and the Taylor polynomial. The third chapter is discussed the concept of mathematical modeling and the concept of linear regression. The central objective is to propose a modeling situation where the function of the characterization theorem in order to be decisive in choosing the model adopted. In this regard it is proposed two situations that address the development of babies and safe piloting of motorcycles: braking. In both cases it is suggested didactic proposed how to work these issues the light of mathematical modeling. The proposal is suitable for students of the first and third year of high school aiming to give applicability to mathematical content the light of reality.